Bone morphogenetic protein 4 and retinoic acid trigger bovine VASA homolog expression in differentiating bovine induced pluripotent stem cells. Issue 2 (25th January 2016) - Malaver‐Ortega, Luis F.; Sumer, Huseyin; Jain, Kanika; Verma, Paul J.
SUMMARY: Primordial germ cells (PGCs) are the earliest identifiable and completely committed progenitors of female and male gametes. They are obvious targets for genome editing because they assure the transmission of desirable or introduced traits to future generations. PGCs are established at the earliest stages of embryo development and are difficult to propagate in vitro—two characteristics that pose a problem for their practical application. One alternative method to enrich for PGCs in vitro is to differentiate them from pluripotent stem cells derived from adult tissues. Here, we establish a reporter system for germ cell identification in bovine pluripotent stem cells based on green fluorescent protein expression driven by the minimal essential promoter of the bovine Vasa homolog ( BVH ) gene, whose regulatory elements were identified by orthologous modelling of regulatory units. We then evaluated the potential of bovine induced pluripotent stem cell (biPSC) lines carrying the reporter construct to differentiate toward the germ cell lineage. Our results showed that biPSCs undergo differentiation as embryoid bodies, and a fraction of the differentiating cells expressed BVH . The rate of differentiation towards BVH ‐positive cells increased up to tenfold in the presence of bone morphogenetic protein 4 or retinoic acid. Finally, we determined that the expression of key PGC genes, such as BVH or SOX2, can be modified by pre‐differentiation cell culture conditions, although this increase is not necessarily mirrored by an increase in the rate of differentiation. Mol. Reprod. Dev. 83: 149–161, 2016. © 2015 Wiley Periodicals, Inc .